(untitled) (Revista Logos Ciencia & Tecnología, 2019)
The waste of food has increased worldwide. Likewise, there is a large population that does not eat properly and can take advantage of these wasted foods. In this way, food banks emerge as a strategy to minimize food waste and increase food security in vulnerable populations. However, they present a problem to assign food to those who request their support. This decision must include several criteria that allow food to go to the organizations and / or populations that need it most. Then, a multicriteria decision model is proposed that integrates the AHP and TOPSIS tools so that a food bank can manage the available resources in the best possible way. Food waste has increased worldwide. Also, there is a large population that is not adequately fed and could take advantage of these wasted food. In this way, food banks emerge as a strategy to minimize food waste and increase food security in vulnerable populations. However, they present a problem to assign food to those who request their support. This decision must consider multiple criteria that allow food to go to the organizations and / or populations that need it most. Then, a multicriteria decision model is proposed that integrates the AHP and TOPSIS tools so that a food bank can manage the available resources in the best possible way. The model uses the AHP for the weighting of the criteria that will be considered relevant for the decision of the food bank's assignment to the requesting institutions, and TOPSIS is used to assess these criteria in the alternatives that request support. It is a model that allows supported and dynamic decision making that was positively valued by a Food Bank in Colombia.